Variation in Fruit Morphological Traits of Jatropha curcas at Stand and Tree Level - Malhotra, Kshitij; Kumar, Dinesh; Pandey, Vidya Dhar (Indian Forester, 2012)
Nine fruit morphological traits were studied in ten stands of Jatropha curcas sp well as at tree level. Significant differences werefound among stands for fruit length, fruit diameter, pericarp weight per fruit, seed: fruit weight ratio, kernel: fruit weight ratio and pericarp: fruit weight ratio traits while all morphological traits showed significant differences among trees within stands. The estimation of the variance components, however, revealed that the fruit traits, especially weight traits viz. fruit weight, total seed weight per fruit and total kernel weight per fruit have negligible contribution from stands and small contribution from trees.Maximum variationwas found among fruits within trees (i.e.at fruit levelorerror).Pericarp weight per fruit and fruit ratio traits (i.e. seed: fruit weight ratio, kernel: fruit weight ratio and pericarp: fruit weight ratio) were affected to small extent by stand per se. The repeatability of all fruit traits at tree level were also low to moderate (0.105 to 0.278).